(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Collaborative learning is an educational approach, which can be easily applied to a business setting. However, it is often unconsciously implemented in organizations in general, whereas, some of it aspects are not perceived at all as new contributions. In order to take advantage of all its benefits, it should be a guided process. Based on an assessment of theory, this conceptual paper provides the classification of collaborative learning in destination management grounded on a few dimensions and several implications related to its proper application. Through a comparison, it proposes an enhanced model of collaborative learning in line with the requirements of managing tourism destinations. The concept of collaborative learning represents a good fit for enhancing stakeholder engagement, improving collective education and reaching consensus. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.